2015
DOI: 10.1007/s40593-015-0065-9
|View full text |Cite
|
Sign up to set email alerts
|

Face-to-Face Interaction with Pedagogical Agents, Twenty Years Later

Abstract: introduced and surveyed a new paradigm for interactive learning environments: animated pedagogical agents. The article argued for combining animated interface agent technologies with intelligent learning environments, yielding intelligent systems that can interact with learners in natural, human-like ways to achieve better learning outcomes. We outlined a variety of possible uses for pedagogical agents. But we offered only preliminary evidence that they improve learning, leaving that to future research and dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
118
0
20

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(140 citation statements)
references
References 26 publications
2
118
0
20
Order By: Relevance
“…Although the instructional effectiveness of onscreen pedagogical agents has been a topic of interest for the past 20 years (Cassell, 1Sullivan, Prevost, & Churchill, ; Dehn & van Mulken, ; Heidig & Clarebout, ; W. L. Johnson & Rickel, ; W. L. Johnson & Lester, ; Mayer & DaPra, ; R. Moreno et al, ; Schroeder & Adesope, ; Schroeder, Adesope, & Gilbert, ; Veletsianos & Russell, ; Wang, Li, Mayer, & Liu, ), an important remaining issue concerns how best to render the basic characteristics of the agent, such as gender, ethnicity, and age (Baylor & Kim, ; Hoogerheide, Loyens, & van Gog, ; Hoogerheide, van Mermeskerken, van Nassau, & van Gog, ; Kim & Baylor, ; R. Moreno & Flowerday, ; Ozogul, Johnson, Atkinson, & Reisslein, ; Rosenberg‐Kima, Plant, Doerr, & Baylor, ). Kim and Lim () found that learner gender was a significant factor in the learner's evaluations of a pedagogical agent with females holding more positive attitudes towards agents.…”
Section: Introductionmentioning
confidence: 99%
“…Although the instructional effectiveness of onscreen pedagogical agents has been a topic of interest for the past 20 years (Cassell, 1Sullivan, Prevost, & Churchill, ; Dehn & van Mulken, ; Heidig & Clarebout, ; W. L. Johnson & Rickel, ; W. L. Johnson & Lester, ; Mayer & DaPra, ; R. Moreno et al, ; Schroeder & Adesope, ; Schroeder, Adesope, & Gilbert, ; Veletsianos & Russell, ; Wang, Li, Mayer, & Liu, ), an important remaining issue concerns how best to render the basic characteristics of the agent, such as gender, ethnicity, and age (Baylor & Kim, ; Hoogerheide, Loyens, & van Gog, ; Hoogerheide, van Mermeskerken, van Nassau, & van Gog, ; Kim & Baylor, ; R. Moreno & Flowerday, ; Ozogul, Johnson, Atkinson, & Reisslein, ; Rosenberg‐Kima, Plant, Doerr, & Baylor, ). Kim and Lim () found that learner gender was a significant factor in the learner's evaluations of a pedagogical agent with females holding more positive attitudes towards agents.…”
Section: Introductionmentioning
confidence: 99%
“…According to Realdon, Zurloni, Confalonieri, Mortillaro, and Mantovani (2006), scripting different ad hoc perspectives is a fundamental prerequisite for a narrative structure in order to reproduce both the flexibility and regularity of communicative exchanges. In 'Face-to-Face Interaction with Pedagogical Agents, Twenty Years Later, ' Johnson and Lester (2016) evaluate the evolution of features of pedagogical agents over two decades. They present the possibility of interactive natural language dialogue by combining advances in natural language understanding and dialogue management.…”
Section: Learning Environments For Communication Skillsmentioning
confidence: 99%
“…Daphne Koller of Coursera holds a similar notion, 'people are social animals…they like to learn in groups and they like to learn from people', he declared and concluded that despite tremendous technology-aided achievement in education like that of Coursera, there is no surety that 'AI can do everything that a human college professor can do' (Johnson, 2016). He cited content creation, providing inspiration for learning, and attending to what he described as the 'really challenging questions' as things only human teachers will be able to do in line with the demands of human-human social interaction that are essential for learning.…”
Section: Challenges With Independent Robot Teachersmentioning
confidence: 99%
“…Though studies have demonstrated that the agentic appearance and affective capabilities has implications for students' learning (Jensen, Jordine, and Wilson 2011;Johnson and Lester 2016), agentic size (in terms of physical robot) has not been the focus of studies. Robot size (miniature versus life-size) does not represent a major factor in our design due to cost, however, we have in mind to assess student expectations regarding this in future studies.…”
Section: Teacher Personalitymentioning
confidence: 99%